IMPROVING STUDENT LEARNING OUTCOMES USING AUDIO VISUAL MEDIA ON PLANT PARTS AND THEIR FUNCTIONS TOPIC AT CLASS 4 SD NEGERI 1 PAGAR ALAM OF PAGAR ALAM CITY - Anggela Nanda Rahma Saputra; Ulil Azmi (Journal of Higher Education and Academic Advancement, 2024)
Learning in the digital era demands innovative and interactive approaches to increase student interest and understanding. This research aims to measure the effectiveness of using audio-visual media in improving the learning outcomes of class IV students at SD Negeri 1 Pagar Alam on plant parts and their functions. Using a collaborative classroom action research (PTK) method consisting of two cycles, this research involved 22 students. Data obtained from observations and learning evaluations. In the pre-cycle, only 22.73% of students reached the KKM. After applying image media in cycle I, the percentage increased to 54.55%. The use of audio visual media in cycle II showed a significant increase, with 86.36% of students reaching or exceeding the KKM. These results indicate that audio visual media is effective in improving student learning outcomes. Apart from that, this media is able to make learning more interesting, increase engagement, and facilitate students' understanding of scientific concepts. This research provides practical benefits for students and teachers, especially in creating a more dynamic and relevant learning environment in the digital era